A new method to predict refracture risk after locking compression plate removal of clavicle shaft - Shuai Han; Qinghe Wang; Fang Tan; Kun Li; Shuang Li (BMC Surgery)
Abstract Background The incidence rate of subsequent refracture after removal of the implant in mid-shaft clavicle fracture patients is relatively high. This can lead to additional medical costs and cause doctor-patient dispute. This study tries to introduce a new method to predict the refracture risk of the clavicle after hardware removal. Methods A retrospectively review of 244 patients who had undergone ORIF with LCP for mid-shaft clavicle fractures, and had hardware removal surgery after bony union from January 2013 to September 2022 at our hospital was performed. We evaluated basic demographic characteristics, and analyzed the mean gray value of screw holes with the Image J software, which was extensively used in Western-blot analysis. Results Our study showed that about 2.0% patients suffered refracture after removal of the LCP. For the first time we found obvious differences in remaining bone ratio and the index of remaining Clavicle intensity between the two groups. There was no difference between groups with regards to preoperative characteristics. Conclusions Surgeons should mention that there is a relatively higher possibility of refracture rate and emphasize a proper immobilization after secondary operation. There are no significant preoperative demographics parameters associated with refracture. The mean gray value of screw holes on immediate postoperative X-ray can be a potential clinical predictor for refracture rate after LCP removal.